2011
DOI: 10.1186/1471-2334-11-274
|View full text |Cite
|
Sign up to set email alerts
|

Potential immunomodulatory effects of latent toxoplasmosis in humans

Abstract: BackgroundAbout 30% of the population worldwide are infected with the protozoan parasite Toxoplasma gondii. Latent toxoplasmosis has many specific behavioral and physiological effects on the human organism. Modified reactivity of the immune system has been suggested to play a key role in many of these effects. For example, the immunosuppression hypothesis explains the higher probability of the birth of male offspring observed in Toxoplasma-positive humans and mice by the protection of the (more immunogenic) ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
38
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 29 publications
2
38
2
Order By: Relevance
“…Infected men rated the smell of cat urine as relatively more pleasant while infected women rated it as relatively less pleasant compared with noninfected controls (Flegr et al, 2011). Using urine from four other animal species (tiger, dog, horse, brown hyena), a similar but weaker effect was observed for hyena urine.…”
Section: Influence Of Toxoplasma On the Human Phenotypementioning
confidence: 59%
See 2 more Smart Citations
“…Infected men rated the smell of cat urine as relatively more pleasant while infected women rated it as relatively less pleasant compared with noninfected controls (Flegr et al, 2011). Using urine from four other animal species (tiger, dog, horse, brown hyena), a similar but weaker effect was observed for hyena urine.…”
Section: Influence Of Toxoplasma On the Human Phenotypementioning
confidence: 59%
“…The children of Toxoplasma-infected mothers have lower rates of motor development in the first 18months of life (Kaňková et al, 2012). Most differences in the reproductionassociated traits between infected and non-infected women can be explained as being a result of immunosuppression and the resulting (expected) decrease in the stringency of embryo quality control (Neuhäuser and Krackow, 2007), which has been observed in both humans (Flegr and Stříž, 2011) and mice (Kaňková et al, 2010a) with latent toxoplasmosis. A large proportion of embryos with various developmental defects, as well as a large percentage of more immunogenic male embryos, are aborted in the early weeks of pregnancy.…”
Section: Influence Of Toxoplasma On the Human Phenotypementioning
confidence: 99%
See 1 more Smart Citation
“…At the same time, psychomotor performance of infected Rh-positive homozygotes and especially of infected Rh-negative homozygotes was much poorer than that of corresponding controls (Novotná et al, 2008). It has been shown that toxoplasmosis has various effects on human physiology and some of these effects, such as increase of testosterone (Flegr et al, 2008a,b) or partial immunosuppression (Flegr and StříŽ, 2011), could have a positive impact on human performance and health in certain situations. It must be remembered that our population of Rh-positive women represents a mixture of homozygotes and heterozygotes.…”
Section: Discussionmentioning
confidence: 99%
“…It is known, however, that latent toxoplasmosis has specific immunomodulatory effects on immune system of infected humans and mice (Flegr and Stříž, 2011;Kaňková et al, 2010) which could influence the risk and the course of other infections such as borreliosis. An alternative explanation could be based on the hypothesis of the existence of a vector shared by both pathogens.…”
Section: Discussionmentioning
confidence: 99%